Chironomidae (Diptera) larvae in Cip Dam lake (Elazi?) - Akil, Ayda; Ayvaz, Yusuf; Şen, Durşun (TUBITAK, 1996)
In this study, the Chironomidae (Diptera) larvae collected of Cip Dam lake have been investigated. Our result have established the presence of 17 species belonging to subfamilies Tanypodinae, Chironominae and Ortocladiinae. The most abundant species, namely Paratanytarsus lauterborni K. contained 13% of total larvae numbers, whereas the most scarce species, Virgotanytarsus arduensis G. cousisted of 0.7% of total larvae, only. We have concluded that the highest number of larvae occurred in summer, whereas the lowest number was found in winter.
Cip Baraj Gölü (Elazi?) Chironomidae (Diptera) larvalari
Keywords: Turkey, Elazig, Cip Dam Lake; Chironomidae; Chironominae; Diptera; Ortocladiinae; Paratanytarsus lauterborni; Tanypodinae; Virgotanytarsus arduensis; abundance; fly larva